THE INFLUENCE OF PERSON ORGANIZATION FIT, QUALITY OF WORK LIFE AND CAREER DEVELOPMENT ON AFFECTIVE COMMITMEN MODERATED JOB SATISFACTION (Case Study on Production Departement Employees of PT. Real Glass Semarang) - Paramita, Patricia Dhiana; Harini, Cicik (Jurnal Ilmiah Fokus Ekonomi, Manajemen, Bisnis & Akuntansi (EMBA), 2022)
Every organization is required to be able to maintain the affective commitment of its employees, because this will make employees have high loyalty and are willing to sacrifice for the benefit of their organization. The research object is PT. Real Glass Semarang, a company engaged in the manufacture of dark grey glass using modern technology,namely sheet glass and float glass. PT. Real Glass in order to continue to exist in the midst of intense competion with other comapanies engaged in the same field, the copany experienced a problm phenomenon, wh the affective commitment possessed by employees in the production section was low. It is suspected that is motivated by the low pn orgizati fit, quality of work life and career development in the company. The research objective was to determine the impact of person organization fit, quality of work life and career development on affective commitment partially and simultaneously and to find out wether job satisfaction strengthens the impact of person organization fit, quality of work life and career development on affective commitment.The population of this research is 88 employees who work in the production departement of PT. Real Glass Semarang, while the sampling technique is a cencus, where the entire selected population is used as a sample.The analysis technique used is multiple linear regression with Moderated Regression Analysis (MRA). The calculation results show that person organization fit, quality of work life and career development partially and simultaneously have a positive and significant impact on affective commitment. Job satisfaction partially strengthens the impact of person organization fit, quality of work life and career development on affective commitment. There needs to be a special policy from the management of PT. Real Glass Semarang in order to increasethe affectice commitment of production employees, by increasing employee job satisfaction, so that il will have a positive impact on increasing person organization fit, quality of work life and career development.Keywords : affective commitment, career development, job satisfaction, person organization fit and quality of work life